Encyclopedia of Inorganic Chemistry 2005
DOI: 10.1002/0470862106.ia055
|View full text |Cite
|
Sign up to set email alerts
|

Copper Proteins: Oxidases

Abstract: Oxidases are enzymes that use dioxygen as the electron acceptor in oxido‐reduction reactions. Many members of this enzyme class (EC 1.) rely on the Cu 1+ /Cu 2+ redox cycle of copper prosthetic group(s) in their catalysis of the electron transfer from reducing substrate to O 2 . Those copper oxidases that catalyze the four‐electron reduction of O 2 to 2H 2 O are known as multicopper oxidases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 84 publications
1
32
0
Order By: Relevance
“…This was the first report of cuprous oxidase activity attributable to a eukaryotic ferroxidase; this activity has been reported also in the copper resistance protein in Escherichia coli, CueO (22,23). We have suggested that MCO proteins that exhibit reactivity toward lower valent metal ions be designated metallooxidases (4,20).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…This was the first report of cuprous oxidase activity attributable to a eukaryotic ferroxidase; this activity has been reported also in the copper resistance protein in Escherichia coli, CueO (22,23). We have suggested that MCO proteins that exhibit reactivity toward lower valent metal ions be designated metallooxidases (4,20).…”
mentioning
confidence: 78%
“…The specificity an MCO has toward the one-electron donor (reducing) substrate is determined by the relative rate of electron transfer from a given substrate to the T1 Cu(II), which is the acceptor site in this outer sphere ET process (2,4,44). An outer sphere electron transfer reaction rate is analytically given by the Marcus equation, Equation 1 (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cp is a member of a large family of proteins (Ͼ500 homologs found in all three super kingdoms) known as multicopper oxidases (MCOs). MCOs that contain Ϸ500 amino acid residues are composed of three Greek key ␤-barrel cupredoxin (plastocyanin-like) domains (5) that come together to form three spectroscopically distinct copper binding sites termed type 1 (T1), type 2 (T2), and type 3 (T3) (6,7). With Ͼ1,100 residues, Cp differs from Fet3p through duplication of this trimeric cupredoxin assembly (8).…”
mentioning
confidence: 99%